PENGARUH BUDAYA KERJA, KOMPETENSI PROFESIONAL GURU DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KEPUASAN KERJA - Respy Desmaryani; Ali Idrus; Erisa Kurniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of work culture, teachers’ professional competence, and transformational leadership of the principal on teachers’ job satisfaction at SMAN 8 Tanjung Jabung Timur. The research employed a quantitative approach using an ex post facto method, as there was no treatment applied to the independent variables and the study was conducted based on conditions that had already occurred in the field. The sample consisted of 30 teachers selected using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 31. The results showed that partially, work culture did not have a significant effect on teachers’ job satisfaction (sig. 0.137 > 0.05), and teachers’ professional competence also did not have a significant effect (sig. 0.609 > 0.05). In contrast, the principal’s transformational leadership had a positive and significant effect on teachers’ job satisfaction (sig. 0.017 < 0.05). Simultaneously, work culture, teachers’ professional competence, and transformational leadership of the principal had a significant effect on teachers’ job satisfaction (sig. 0.028 < 0.05). These findings indicate that teachers’ job satisfaction is more strongly influenced by the principal’s leadership factor compared to work culture and professional competence individually. Therefore, the implementation of inspirational, supportive, and visionary transformational leadership is an important strategy to enhance teachers’ job satisfaction and support the improvement of educational quality in schools.